POSITIVE ETHNIC IDENTITY SEBAGAI MEDIATOR ANTARA SOSIALISASI ETNIS DENGAN RESILIENSI KELUARGA ETNIS TIONGHOA-INDONESIA - Rosyana Lieyanty; Sri Redatin Retno Pudjiati (Universitas Kristen Maranatha, 2022)
Family resilience is a positive adaptation that is grown through the functioning of family members. This study aims to determine the role of positive ethnic identity in mediating the relationshop between family racial-ethnic socialization and family resilience in the Chinese-Indonesian early adult group. Participants consisted of 338 individuals aged 17-30 years. The measuring instruments used are the Walsh Family Resilience Questionnaire, Asian American Parental Racial-Ethnic Socialization, and Multidimensional Inventory of Black Identity which were adapted into the context of Chinese-Indonesian ethnicity. The result show that family ethnic-racial socialization affects family resilience directly or indirect through positive ethnic identity mediation. Further research can analyze the intencity of family ethnic-racial socialization to find out how much socialization level is needed to achieve resilience in the family.